INVESTIGATING THE VOLUME OF MENTAL HEALTH EMERGENCY CALLS IN THE WELSH AMBULANCE SERVICE TRUST (WAST) AND DEVELOPING A PRE-HOSPITAL MENTAL HEALTH MODEL OF CARE FOR APPLICATION AND TESTING. Issue 5 (18th April 2015) - Morisson-Rees, Sian; Whitfield, Richard; Evans, Sherrill; Snooks, Helen; Huxley, Peter; John, Ann; Baker, Chris; Engamba, Serge; Rees, Nigel
Abstract : Background: Limited published evidence indicates a significant impact from mental health related calls on ambulance services (AS), however available routine data appear to underestimate the amount of these calls and the resources spent in response. Paramedics have reported feeling ill-equipped for informed clinical decision-making in mental health cases: leaving at home can risk self harm, but conveying to an emergency departments is often not the most appropriate place for patients with mental distress and unnecessarily ties up resources. Objective: To investigate mental health 999 calls in WAST and design a relevant model-of-care for testing. Method: We examined the Patient Clinical Records (PCR) completed by paramedics on scene for all calls handled by WAST in April 2012. We extracted an electronically generated 10% random sample and coded the narrative section based upon ICD 10 codes. We mapped statutory mental health services in three different ambulance trusts. A panel of experts identified the critical factors and devised a generic model of care based upon an ideal model to support paramedics and the pragmatics of existing services. Results: In April 2012 WAST handled 28, 328 999 calls, with 1642 (5.8%) recorded with a mental health condition code. In the random sample we found 164 (10.5%) calls related to mental health problems and estimate the volume to be 2974 per month. Each category of mental health problem had a conveyance rate of over 80%, with the exception of anxiety (61.6%) The alternative statutory services available varies by AS area, however enough commonality existed to reach consensus and design a generic mental health model of care. Conclusion: Both dispatch and on-scene condition codes underestimate the volume of mental health related emergency calls by nearly half. Our model of care provides considerable potential to support paramedics to assess and reduce transfers to emergency departments through access to pre-existing community care provision.